Análisis del tratamiento informativo a los casos de xenofobia en Diario la Prensa de Riobamba - año 2020. - Saavedra Armas, Vanessa Estefania (2022)
This research project investigates the "Analysis of the informative treatment of xenophobia cases in Diario “La Prensa” of Riobamba - the year 2020" the objective was to know how Diario “La Prensa” addresses content related to xenophobia cases, taking into account that the discourse used can produce a specific reaction to the readers. The general objective was to analyze the informative treatment of xenophobia cases in Diario “La Prensa” of Riobamba in 2020. The research employed a quantitative-qualitative methodology; the techniques used were documentary review and interview; a structured interview guide, a web visit guide, and a content analysis matrix were used as instruments. As a result, it was found that the discourse used in the publications of Diario “La Prensa” 2020 on cases of xenophobia; the discourse maintained in the articles is negative, taking into account that articles that incite xenophobia were also analyzed, obtaining 71% in all that was published during the year, which explains that in Diario “La Prensa”, this intentionality prevailed. On the other hand, it could be evidenced that 61% of official sources are used; therefore, the aim is to maintain a more excellent dialogue with the authorities about the events recorded, 26% were given openness to primary sources; however, 11% of the articles do not have sources which means that the fact does not have a basis that delegates the news is trustworthy.